The impact of the communicative approachon the teaching-learning process of english as a foreign language to students from second year of general high School at Instituto Nacional Albert Camus, in San Salvador, from january to june 2016 - Arias Ramos, María Idalia; Barahona Teodoro, Evelyn Josefina; Martínez Martínez, Ana Gabriela (2024)
The following describes briefly the approaches, principles, and methods as they have been developed through history. Approach is defined as a set of assumptions or philosophy concerning a language, it provides a point of view of the nature of language teaching and learning. Principle is a basic truth or theory: an idea that forms the basis of something. Method is the “how” the teaching is to be conducted; it is the realization of an approach. Grammar translation method is a method of foreign or second language teaching which makes use of translation and grammar study as the main teaching and learning activities, its main goal is to be able to read literature in target language to learn grammar structures and vocabulary. This method is derived from traditional approaches to the teaching of Latin and Greek in the early 1500s. Some activities include translating literary passages from one language to another, memorizing grammar rules and learn by heart language equivalents to target language vocabulary. Some characteristics include: the meticulous analysis of target language and grammar, students are taught list of separated word and not into context and the class is mostly teacher-centered. Another method: The Direct had its origins in Germany and France around 1900 and contrasts with the grammar–translation method. The main goal is to communicate in the target language by thinking in the target language. The Direct Method was born as a reaction against the Grammar Translation Method GTM. It allows students to comprehend meaning directly from the target language context since translation is not necessary. Grammar is not taught, it is acquired unconsciously through practical use. A third method, the Audio –Lingual Method (Aura-Oral Approach) was based on the belief of learning through acquisition of patterns. Its main goal is to use the target language communicatively, over learn it to then produce it automatically as a habit, without over thinking until it becomes native language habits. It was highly developed by B.F. Skinner (Diane Larsen, Freeman, 2000). As the learner repeats patterns until he or she is able to produce them spontaneously: the student can replace some of the words to make new sentences. The teacher always controls this behavior, provides models and reinforces correct responses. A fourth method, The Total Physical Response or TPR was developed by James Asher, cited in Richards & Rodgers 2001, p. 76. Students are able to get in contact with a relaxed, motivated, enjoyable learning experience that minimizes stress that might affect while learning a foreign language.